2017
DOI: 10.24247/ijasroct201753
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Functional Properties of Hylocereus Undatus (White Dragon Fruit)

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…Thus, no result of tannins presence was obtained. This was confirmed by a previous study [24] in which they also stated that flavonoids and saponins were only present in the Hylocereus undatus foliage. Based on these findings, it can be concluded that the presence of saponins and flavonoids in Hylocereus undatus foliage is likely to be temperature-independent as evidenced via both oven-dried and open air-dried methods in the study.…”
Section: Resultssupporting
confidence: 85%
“…Thus, no result of tannins presence was obtained. This was confirmed by a previous study [24] in which they also stated that flavonoids and saponins were only present in the Hylocereus undatus foliage. Based on these findings, it can be concluded that the presence of saponins and flavonoids in Hylocereus undatus foliage is likely to be temperature-independent as evidenced via both oven-dried and open air-dried methods in the study.…”
Section: Resultssupporting
confidence: 85%
“…For patients with Type II Diabetes, the use of red dragon fruit can reduce blood glucose levels. The substance that lowers blood sugar levels in red dragon fruit is glucose 52 .…”
Section: Antidiabetic Activitymentioning
confidence: 99%
“…Email: jesmartinez@uv.mx, https://orcid.org/0000-0003-3049-5289 and peel of H. polyrhizus fruits, attributed to its content of polyphenols and ascorbic acid. Polyphenols or phenols, due to effects, have been considered antagonistic to resist free radicals, which deteriorate food and our body [8]. High antioxidant activity was found in the ethanolic extract in the peel of H. undatus fruit [8].…”
Section: Introductionmentioning
confidence: 99%
“…Polyphenols or phenols, due to effects, have been considered antagonistic to resist free radicals, which deteriorate food and our body [8]. High antioxidant activity was found in the ethanolic extract in the peel of H. undatus fruit [8]. Various authors such as Omidizadeh et al [9], Sudha et al [8], and Ibrahim et al [6] analyzed juice and pulp of Hylocereus with white and red pulp, which is recommended as a promising source of alternative medicine, antioxidant and antidiabetic.…”
Section: Introductionmentioning
confidence: 99%